ANALISIS MANAJEMEN PAJAK PADA PERUSAHAAN ADIPRIMA SURAPRINTA : STUDI KASUS PADA INDUSTRI PERCETAKAN - Sukma Ali Winata; Miya Dewi Suprihandari (PUTRA JAWA PUBLISHER, 2024)
This study aims to analyze the implementation of tax management at PT Adiprima Suraprinta, one of the leading printing companies in Indonesia. Tax management is an important element in corporate financial management, especially in the printing industry which has capital-intensive characteristics and faces fierce competition. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews with the management of PT Adiprima Suraprinta, document review, and field observations. Data analysis was carried out descriptively to identify the tax management strategies applied, the factors that influence them, and their impact on the company's financial performance. The results showed that PT Adiprima Suraprinta implemented several tax management strategies, such as utilizing tax incentives, managing fixed assets, and optimizing tax planning. Factors that influence the implementation of tax management in this company include capital structure, industry characteristics, and government tax policy. The implementation of effective tax management is proven to increase the efficiency of the tax burden and have a positive impact on company profitability. The findings of this study can provide valuable insights for other companies in the printing industry in strategically managing tax management to improve competitiveness and financial performance.